2022
DOI: 10.3389/fcomm.2022.844862
|View full text |Cite
|
Sign up to set email alerts
|

Within-Speaker Perception and Production of Two Marginal Contrasts in Illinois English

Abstract: The notion of marginal contrasts and other gradient relations challenges the classification of phones as either contrastive phonemes or allophones of the same phoneme. The existence of “fuzzy” or “intermediate” contrasts has implications for language acquisition and sound change. In this research, we examine production and perception of two marginal contrasts [ɑ-ɔ] (“cot-caught”), where two original phonemes are undergoing a merger, and [ʌi-aɪ] (“writer-rider”), where a single original phoneme has arguably spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…For example, individuals with better vowel discrimination demonstrate greater contrasts in their vowel productions. 3−6 Other studies have also found evidence within the articulatory domain of speech supporting a perception/production relationship: individuals with better perceptual abilities showed smaller auditory target regions and greater distinctions in production for various articulatory features, including sibilants, 7,8 approximants, 9 Dutch obstruent devoicing, 10 Illinois English /ɑ-ɔ/, 11 and voice onset time (VOT) for stop consonants. 12,13 Despite this well-established relationship within the articulatory domain, the perception/production relationship is less well-defined for voice parameters of speech production, such as pitch.…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals with better vowel discrimination demonstrate greater contrasts in their vowel productions. 3−6 Other studies have also found evidence within the articulatory domain of speech supporting a perception/production relationship: individuals with better perceptual abilities showed smaller auditory target regions and greater distinctions in production for various articulatory features, including sibilants, 7,8 approximants, 9 Dutch obstruent devoicing, 10 Illinois English /ɑ-ɔ/, 11 and voice onset time (VOT) for stop consonants. 12,13 Despite this well-established relationship within the articulatory domain, the perception/production relationship is less well-defined for voice parameters of speech production, such as pitch.…”
Section: Introductionmentioning
confidence: 99%